IT governance framework for e-government initiatives - Kannan, Subarmaniam; Kasmuri, Emaliana; Woods, Peter (2006)
As the penetration of electronic commerce (e-commerce) and electronic business (e-business) occurs in our daily lives, the overall stakeholders of economic growth, including private sector enterprises, governments and society as a whole are beginning to realize the true potential of information technology (IT) and the internet. While the private sector has always ensured that they keep in line with emerging trends, now governments around the globe are also aiming to ensure that all public sector products and services are offered online.Many citizens have a minimal understanding of how government processes are executed or how decisions are made.This lack of awareness and trust can prevent the citizens from actively participating in government services.Thus, E-government security and assurance has become a serious concern of the citizens and private companies who put more reliance on the distributed computing processes in their daily operations.In order to make citizens and private organizations to trust and involves in e-government services, IT Governance should be implemented. As the IT Governance Institute defined that IT governance is the responsibility of the board of directors and executive management. It is an integral part of enterprise governance and consists of the leadership and organisational structures and processes that ensure that the organisation’s IT sustains and extends the organisation’s strategies and objectives.This paper presents an IT governance framework for e-government and introduces an assessment tool designed to measure its effectiveness.The framework builds on the integration between the structural and processes perspectives of IT governance, public services-IT alignment, and senior government executives’ needs.